Dynamics of surface evolution of rutile TiO2(110) after ion irradiation. Issue 3 (3rd April 2019) - Manna, Ashis K.; Solanki, Vanaraj; Kanjilal, D.; Varma, Shikha
ABSTRACT: The dynamics of TiO 2 surfaces evolving under 60 keV Ar + ions have been explored here. Dynamic scaling ansatz, height–height correlation (HHC) model and power spectral density (PSD) model have been applied to investigate the growth mechanisms. The surfaces are growing under non-equilibrium growth processes and three separate domains of evolution have been noticed. Early time growth of the surfaces can be characterized by roughness exponent, α ∼ 0.72 –0.74, and growth exponent, β ∼ 0.3 . Dominance of diffusion is also noticed with Edward Wilkinson (EW) growth scaling. In the next time regime, non-local instabilities get incorporated, due to sputter-induced nanostructuring of the surfaces, resulting in a rapid surface roughening with a high value of β . The surface roughness saturates in late time regime.